2018
DOI: 10.1111/dar.12828
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Khat Knowledge, Attitudes and Perception Scale

Abstract: These results provide initial support of the usefulness of the Khat Knowledge, Attitudes and Perception Scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In addition, another study was carried out in Taiz and Sana'a at local markets and shopping centers to develop a short-term method to evaluate attitudes and perceptions associated with khat. The results showed that knowledge, attitudes, and perceptions among khat users might act as risk or protective factors of khat use, while nonusers recognized the possible harm of khat (Nakajima, Hoffman, Alsameai, Khalil, & al'Absi, 2018). Khat chewing is common in Ethiopia, and a recent meta-analysis revealed that the prevalence of khat chewing among students is also high (Aklilu, Anteneh, & Hiwot, 2014;Gebrie, Alebel, Zegeye, & Tesfaye, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another study was carried out in Taiz and Sana'a at local markets and shopping centers to develop a short-term method to evaluate attitudes and perceptions associated with khat. The results showed that knowledge, attitudes, and perceptions among khat users might act as risk or protective factors of khat use, while nonusers recognized the possible harm of khat (Nakajima, Hoffman, Alsameai, Khalil, & al'Absi, 2018). Khat chewing is common in Ethiopia, and a recent meta-analysis revealed that the prevalence of khat chewing among students is also high (Aklilu, Anteneh, & Hiwot, 2014;Gebrie, Alebel, Zegeye, & Tesfaye, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of women regarding the health effects of khat was evaluated using a series of 18 questions adopted from different literatures ( 70 , 71 ). The knowledge questionnaire was completed on a true/false basis with an extra “I don’t know” option.…”
Section: Methodsmentioning
confidence: 99%
“…Attitude towards khat chewing was assessed using 21 questions. Responses to attitude questions were graded on a 5-point Likert scale, ranging from 1 to 5 (1=strongly disagree, 2=disagree, 3=neutral/not sure, 4=agree, 5=strongly agree) ( 70 , 71 ). The overall attitude of participants was classified as positive if the score is between 80 and 100% (84-105 points), neutral if the score is between 60 and 79% (63-83 points), and negative if the score is less than 60% (63 points).…”
Section: Methodsmentioning
confidence: 99%